Enhancing Phytoremediation Capacity of Iraqi Native Plants through Endophytic Bacteria Inoculation in Polluted - Dikain, Kawther Hussein; Abu-Hadal, Layla S.; Ali, Ali Sabeeh (American Journal of Biology and Natural Sciences, 2025)
All the agricultural pollution of the irrigation basins by industrial waste products, pollution of water with tainted drinking water, and intensive use of agrochemicals have led to land substantial contamination with heavy metals (Pb, Zn, Cu) in Iraq, which threatens food security and the health of the population. The potential of endophyte-improved phytoremediation on the use of native Iraqi flora (Atriplex halimus, Phragmites australis, and Tamarix articulata), with endophyte treatments with Bacillus subtilis and Pseudomonas fluoresces, was studied. As the experiment, a greenhouse study was conducted under controlled conditions, and the soil of agricultural areas with contaminants (Diwaniyah, Basra, and Baghdad) in which the level of metals ordinance has exceeded the standard established by the EPA was used (Pb: 120-450 mg/kg, Zn: 3 00-800 mg/kg, Cu: 50-200 mg/kg).. The endophytic bacteria were grown on plant tissues, tested in terms of metal resistance and properties that encourage growth of plants (e.g., siderophores production, ACC deaminase activity), and identified by 16S rRNA sequencing. It was found that inoculated plants had 4050% of biomass, were able to absorb 23 times more metal and exhibit a 42.5% Pb removal efficiency compared to controls. Atriplex halimus, when mixed with B. subtilis, had the highest Pb uptake (210 mg/kg) but P. fluorescens, in its turn, promoted Zn translocation (TF = 0.7). Significant change of a treatment (ANOVA, *p* < 0.001) and a high relationship between siderophores of bacteria, and absorption of metals ( r = 0.89) were established. The authors conclude that endophyte-mediated phytoremediation is an economical approach to the remediation of Iraqi soils polluted by oil, and it is timely in terms of its application in agricultural activities. Widespread adoption is proposed through field tests and training of the farmers.